Thermal decomposition of wood in oxidizing atmosphere. A kinetic study from non-isothermal TG experiments - Cordero, T; Rodriguez-Maroto, J M (Thermochimica acta, 1991)
The kinetics of thermal decomposition of four wood species in oxygen-bearing atmo- spheres of 5, 10 and 20% molar Oz concentrations have been studied from temperature-pro- grammed experiments carried out at 5, 10 and 20 K mm ’ -* heating rate. Devolatihzation as weII as combustion of the reaminin g solid have been considered to analyze the weight loss curves. The homogeneous volume reaction (VR) model has been used to describe devolatihza- tion, whereas for solid combustion the grain model has been also checked. A two-stage approach has been used to fit the conversion-time curves and to derive the corresponding apparent kinetic parameters. The VR/VR (pyrolysis/combustion) combination provided a better description of the experimental (~-1 curves than the VR/grain combination. Hohn oak and cork oak showed very close reactivities, whereas some differences were observed for aleppo pine and eucalyptus.
Keywords: Aleppo pine; combustion (voyant); Cork oak; EUCALYPTUS; Holm oak; Kinetic model; pyrolysis; Wood